ANALISIS TARIF BUS RAPID TRANSIT (BRT) TRANS SARBAGITA BERDASARKAN BOK, ATP DAN WTP - Suweda, I Wayan; Arisena Wikarma, Kadek (Jurnal Ilmiah Teknik Sipil, 2012)
Tariff analysis was conducted to determine the characteristics of the feasibility of establishing the official tariff of Bus Rapid Transit (BRT) SARBAGITA in terms of Operator’ Vehicle Operating Costs (VOC) and in terms of Users’ Ability To Pay (ATP) and Willingness To Pay (WTP). Secondary data on vehicle operating costs (VOC) was obtained from The Office of Transportation, Communication and Information as a manager of Bus Rapid Transit (BRT) SARBAGITA. Primary data is by conducting survey on board with questionnaires to get the data of Ability To Pay (ATP) and the Willingness To Pay (WTP) of users as a representative community. Based on the results of analysis it was found that with Load Factor of 80% Vehicle Operating Costs (VOC) of BRT SARBAGITA is Rp. 2.500, - per passenger. On the other hand, based on Users’ Ability to Pay (ATP) was obtained Rp. 1,800, - per passenger and the Willingness to Pay (WTP) is Rp. 2.500, - per passenger. Determination of the current official rate of Rp. 3,500, - per passenger is relatively still high and on an average beyond the reach of society.
Keywords: Bus Rapid Transit (BRT), Vehicle Operating Cost (VOC), Ability To Pay (ATP), Willingness To Pay (WTP)